Lap stability, stroke kinematics, and turn performance in female 200 m short-course finals at the 2019 LEN european championships - Oliveira, J. P.; Marinho, D. A.; Sampaio, T.; Barbosa, T. M.; Silva, A. J.; Arellano, R.; Morais, J. E. (Journal of Sports Analytics, 2026)
The aim of this study was to analyse lap performance stability, stroke kinematic variables in the clean swimming phase and turn performance in the finals of the four 200 m short course (SCM) events (freestyle, backstroke, breaststroke, and butterfly). The sample included thirty-two elite female swimmers who competed in the 200 m finals at the 2019 LEN European Short Course Championships in Glasgow. Lap times, stroke kinematics, and turns were analysed using two approaches: (i) official lap time comparison (50 m), and; (ii) comparison of consecutive segments (25 m). Based on the official lap time comparison, performance significantly decreased over time (p < 0.001) with strong effect sizes in all strokes (* 2 between 0.89 and 0.96). Pairwise comparisons between consecutive 25 m segments were not significant. Turn time increased in all four strokes with strong effect sizes (p < 0.001; * 2 between 0.71 and 0.84). The start contributed *6% and turns *52% of the total race time. These findings highlight that traditional pacing analysis based on official splits may lead to misleading interpretations of performance in SCM events. Analysing 25 m segments provides a more accurate representation of race dynamics and contributes to a clearer understanding of pacing stability in short-course swimming.